2021
DOI: 10.1155/2021/6627693
|View full text |Cite
|
Sign up to set email alerts
|

Research on New Types of Suspension Vibration Reduction Systems (SVRSs) with Geometric Nonlinear Damping

Abstract: Firstly, this paper puts forward two new types of suspension vibration reduction systems (SVRSs) with geometric nonlinear damping based on general SVRS (GSVRS), which only has geometric nonlinear stiffness. Secondly, it derives the motion differential equations for the two new types of SVRS, respectively, and discusses the similarities and differences among the two types and GSVRS through the comparison of motion differential equations. Then, it conducts dimensionless processing of the motion differential equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…On this basis, Liu et al [13] explored a new bursting oscillation of this oscillator, employed three cases of excitation patterns for the investigation of the complex bursting behaviors and analyzed the principle behind the slow-bursting responses and the equilibrium stability via the method of multiple scales (MMS). Novel suspension vibration reduction systems with geometric nonlinear damping were put forward by the configuration of four springs with linear stiffness, and their performance for vibration isolation under impact and random excitations was then analyzed via numerical calculations [14]. Li and Cao [15] proposed a smooth and discontinuous oscillatory system with an irrational nonlinearity, obtained the primary resonant solutions though applying the extended averaging method and then illustrated the complicated dynamical behaviors both numerically and experimentally [16].…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, Liu et al [13] explored a new bursting oscillation of this oscillator, employed three cases of excitation patterns for the investigation of the complex bursting behaviors and analyzed the principle behind the slow-bursting responses and the equilibrium stability via the method of multiple scales (MMS). Novel suspension vibration reduction systems with geometric nonlinear damping were put forward by the configuration of four springs with linear stiffness, and their performance for vibration isolation under impact and random excitations was then analyzed via numerical calculations [14]. Li and Cao [15] proposed a smooth and discontinuous oscillatory system with an irrational nonlinearity, obtained the primary resonant solutions though applying the extended averaging method and then illustrated the complicated dynamical behaviors both numerically and experimentally [16].…”
Section: Introductionmentioning
confidence: 99%
“…The vibration-damping system of vehicles was generally divided into active vibration-damping (Teng, 2017;Bai et al, 2018;Yuan, 2022;Ma et al, 2023) and passive vibration-damping (Li et al, 2019;Yuan et al, 2020;Yang et al, 2021;Zhao et al, 2019), and scholars at home and abroad have carried out some researches on the vibration-damping structure of vehicles and achieved better results. Dong (Dong, 2022) constructed a two-stage vibration-damping model of vehicle passive and active suspensions and performed simulation analysis, and found that active vibration-damping had better smoothing performance than passive vibrationdamping.…”
Section: Introductionmentioning
confidence: 99%